2009
DOI: 10.1159/000201110
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Adiponectin Levels Correlates to Growth Response in Growth Hormone-Treated Children

Abstract: Background/Aims: Adiponectin is secreted by adipose tissue and circulates in human plasma at high levels. Decreased adiponectin levels are associated with insulin resistance and obesity. The aim of this study was to investigate whether changes in serum adiponectin levels are related to the growth response, insulin levels and insulin resistance during growth hormone (GH) treatment. Methods: The study included 94 short prepubertal children (19 girls and 75 boys). The mean age at the start of daily GH injections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…Both aging and GH/IGF-1 deficiency were reported to be associated with complex alterations in the secretory phenotype of adipocytes. GH-deficient patients have significantly higher adiponectin and leptin levels than controls (71), and treatment with GH was reported to decrease the levels of both adipokines (72). Similar to findings in GH-deficient humans, we found that GH/IGF-1 deficiency in Lewis dwarf rats was associated with increased adiponectin levels but serum levels of leptin were within the normal range.…”
Section: Discussionsupporting
confidence: 83%
“…Both aging and GH/IGF-1 deficiency were reported to be associated with complex alterations in the secretory phenotype of adipocytes. GH-deficient patients have significantly higher adiponectin and leptin levels than controls (71), and treatment with GH was reported to decrease the levels of both adipokines (72). Similar to findings in GH-deficient humans, we found that GH/IGF-1 deficiency in Lewis dwarf rats was associated with increased adiponectin levels but serum levels of leptin were within the normal range.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, GH suppressed adiponectin secretion in in vitro cultured human adipose tissue (45), and GH treatment of prepubertal short stature children resulted in decreased serum adiponectin levels (46). Collectively these findings raise the intriguing possibility that GH activity may negatively affect adiponectin production or secretion from adipocytes; however, the mechanism underlying this process is as yet unclear.…”
Section: Discussionmentioning
confidence: 97%
“…However, the reports of adiponectin status in GHD or acromegalic patients have been inconsistent resulting from variabilities in the duration of GH deficiency, age of the subjects, dose of GH treatment, and low sample number (Ciresi et al, 2007; Joaquin et al, 2008; Andersson et al, 2009; Oliveira et al, 2010; Ueland et al, 2010). Circulating adiponectin levels in obese laron syndrome adults and young girls, who have a loss-of-function mutation in the GHR rendering them GH-resistant, is two- to five-fold higher than obese controls.…”
Section: Introductionmentioning
confidence: 99%